2015
DOI: 10.1002/tea.21241
|View full text |Cite
|
Sign up to set email alerts
|

Taking advantage of automated assessment of student‐constructed graphs in science

Abstract: We present a new system for automated scoring of graph construction items that address complex science concepts, feature qualitative prompts, and support a range of possible solutions. This system utilizes analysis of spatial features (e.g., slope of a line) to evaluate potential student ideas represented within graphs. Student ideas are then scored with rubrics based upon the knowledge integration framework (Linn & Eylon, 2011). We tested the effectiveness of this system on graphs constructed by 397 8th-12th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Indeed, sometimes, the argument may be made explicitly. In a study exploring the assessment of student-generated graphs in science, Vitale, Lai andLinn (2015, p. 1438) suggested that "relatively high values of Cronbach's α (six items, pre-test: α = 0.70; post-test: α = 0.77) suggest that these items all, at least partially, measured the same factor^(emphasis added). Depending on how the authors intend the qualifier "at least partially", this claim is either misleading or trivial.…”
Section: Misuse Of Alpha To Imply Unidimensionalitymentioning
confidence: 99%
“…Indeed, sometimes, the argument may be made explicitly. In a study exploring the assessment of student-generated graphs in science, Vitale, Lai andLinn (2015, p. 1438) suggested that "relatively high values of Cronbach's α (six items, pre-test: α = 0.70; post-test: α = 0.77) suggest that these items all, at least partially, measured the same factor^(emphasis added). Depending on how the authors intend the qualifier "at least partially", this claim is either misleading or trivial.…”
Section: Misuse Of Alpha To Imply Unidimensionalitymentioning
confidence: 99%
“…Thus, for critique as for comprehension many students drew on superficial criteria (such as readability) and failed to incorporate their knowledge of the science (such as climate trends) into their response. Instructional studies that emphasize knowledge integration show that it is possible to improve the ability to critique graphs (Chang and Linn 2013;Svihla and Linn 2012;Vitale et al 2015).…”
Section: Critique Itemsmentioning
confidence: 98%
“…To implement this type of item, we took advantage of the WISE graphing tool that provided students with a predefined set of axes and an intuitive point-plotting interface as well as a method for designing automated scoring of the resulting graph (Vitale et al 2015). Since the axes were predefined for the students, the automatic scoring only scored the actual lines the students constructed, and not the other basic graph elements (e.g., axes, axes titles).…”
Section: Graph Construction Itemsmentioning
confidence: 99%
See 2 more Smart Citations